The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/jp5104164
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structures and Transport Properties of n-Type-Doped Indium Oxides

Abstract: Electrical and optical properties of transparent conducting oxides (TCOs) are of essential importance for optoelectronics. Electronic structures are keys to the understanding of these properties. The geometrical and electronic structures of body-centered cubic In 2 O 3 n-typedoped by Group 14 and fifth-period main group elements (Sb, Te and I) are systematically investigated. The calculated electronic structures reveal a good hybridization between the O-2p states and the s-states of Si, Ge and Sn, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 44 publications
10
22
0
Order By: Relevance
“…In2O3. This is in agreement with a previously reported DFT value of 0.90 eV [21] , but notably underestimates -as expected for DFT [22] the experimental value of ≥ 2.7 eV for a single crystal. [23] From the partial density of states ( Figure S10 states, and we found that the addition of Zr does not cause hybridization with these CBM states.…”
Section: Figure 2csupporting
confidence: 93%
See 1 more Smart Citation
“…In2O3. This is in agreement with a previously reported DFT value of 0.90 eV [21] , but notably underestimates -as expected for DFT [22] the experimental value of ≥ 2.7 eV for a single crystal. [23] From the partial density of states ( Figure S10 states, and we found that the addition of Zr does not cause hybridization with these CBM states.…”
Section: Figure 2csupporting
confidence: 93%
“…206), using a cut-off energy of 500 eV and 2  2  2, 4  4  4, and 8  8  8 k-meshes for the structure relaxation, selfconsistent calculation, and non-self-consistent calculation, respectively. In the structure relaxation, we use the Perdew-Burke-Ernzerhof [21] Figure S1. UV-vis-NIR transmittance and absorptance spectra of the IZRO films depending on the process pressure for a) before and b) after annealing, r(O2) for c) before and d) after annealing, the thickness of the film e) before and f) after annealing, influence of the postannealing temperature.…”
Section: Dft Modellingmentioning
confidence: 99%
“…All the examples given in this section so far concerned Sn doped indium oxide, as it is currently the benchmark materials for inorganic transparent electrodes. However, it has been shown that indium oxide can also be efficiently doped by other elements such as Si, Ga or Mo [34][35][36][37] .…”
Section: Figure 3 Evolution Of Resistivity Carrier Concentration and Carrier Mobility (Hall Mobility) Inmentioning
confidence: 99%
“…In the absence of experimental data, an estimate of the relaxation time may be obtained by Here, μ, e, τ, and m * denote the carrier mobility, elementary charge, average relaxation time, and effective mass, respectively. The effective mass can be obtained by fitting the conduction band minimum by a parabola [30,31]   where ε(k), ħ, and k represent the band dispersion, the reduced Planck constant, and a wave vector, respectively. An effective mass of 0.42m 0 (m 0 : rest electron mass) is therefore obtained, which is slightly larger than those of the typical transparent conducting oxides (from 0.14m 0 to 0.35m 0 ), such as In 2 O 3 , SnO 2 , Ga 2 O 3 , and ZnO [29,[31][32][33].…”
Section: The Transport Properties Of H-adsorbed 2d β-Gasmentioning
confidence: 99%
“…The effective mass can be obtained by fitting the conduction band minimum by a parabola [30,31]   where ε(k), ħ, and k represent the band dispersion, the reduced Planck constant, and a wave vector, respectively. An effective mass of 0.42m 0 (m 0 : rest electron mass) is therefore obtained, which is slightly larger than those of the typical transparent conducting oxides (from 0.14m 0 to 0.35m 0 ), such as In 2 O 3 , SnO 2 , Ga 2 O 3 , and ZnO [29,[31][32][33]. The larger effective mass likely arises from the relatively increased contribution of the localized 3p states of the anions vs. the delocalized 4s states of the cations in 2D GaS, as shown in Fig.…”
Section: The Transport Properties Of H-adsorbed 2d β-Gasmentioning
confidence: 99%